Żydowskie placówki przedszkolne na Dolnym Śląsku prowadzone przez Centralny Komitet Żydów w Polsce w latach 40. i 50. XX w. - zarys problematyki - Techmańska, Barbara (Uniwersytet Wrocławski Wydział Nauk Historycznych i Pedagogicznych. Instytut Historyczny, 2020)
The article presents the history of Jewish kindergartens and after-school care centers on the postwar Lower Silesia, and documents the struggle of the Jewish community regarding childcare. It is focused on institutions subordinate to Central Committee of Polish Jews, and directly – to the Provincial Committee of Polish Jews in Wrocław. It present the housing conditions, the staff and rules of operation of the Lower Silesian establishments, including those in Wrocław and Legnica
Keywords: regionalizm; region; Śląsk; Polska; Czechy; Niemcy; czasopismo regionalne; czasopismo historyczne